The results of introduction of arboreal decorative plants in lakeside-gully landscape area of Dendropark Trostjanets - V.A. Medvedev; O.O. Iljenko (Інтродукція Рослин, 2013)
The dynamics of strange arboreal plants in lakeside-gully area of dendropark Trostjanets is investigated. It is presented a numerical score of their viability on the genesic development indexes, winter resistance and drought-resistingness. The estimation of success of introduction of 140 species and cultivars of arboreal plants in lakeside-gully area of denropark is given.